Navigating the complexities of teaching rounds: balancing educational and patient-centered objectives - Yang Li; Lu Lu; Yanming Yin; Aijun Wang; Denghui Huang; Wenjiang Yang; Wenjiang Yang (Frontiers in Medicine)
BackgroundTeaching rounds are a fundamental component of medical education, offering essential clinical learning opportunities for students while ensuring high-quality care for patients. Despite their importance, the psychological and emotional experiences of participants—attending physicians, interns, and patients—during these rounds remain underexplored. This study addresses this gap by examining the impact of patient presence on the learning environment, focusing on three key themes: psychological comfort and anxiety, cognitive load management, and emotional engagement and detachment.Material and methodsA design-based research approach was employed, conducted in a surgical ward affiliated with a medical college. The study involved 40 participants, including attending physicians, interns, and patients. Data were collected through 40 in-depth interviews, with analysis focusing on the experiences and perspectives of all parties involved.ResultsThe findings reveal that transparency in communication is crucial for building trust but can also induce anxiety among both trainees and physicians due to the scrutiny of their actions. Managing cognitive load was identified as a significant challenge, particularly for interns who must balance learning with patient interaction. Emotional engagement is vital for effective patient care but must be carefully balanced with professional detachment to maintain clinical objectivity.ConclusionThis study contributes to the understanding of the complex dynamics in teaching rounds, emphasizing the need for strategies that balance educational goals with patient-centered care. The insights gained offer valuable guidance for enhancing the learning environment in medical education.